Optimasi Penempatan Ruang Sidang Skripsi Menggunakan Algoritme Genetika - Nelli Nur Rahma; Budi Darma Setiawan; Agus Wahyu Widodo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The main problem that often happen in room placement final presentation for thesis in Computer Science Faculty is where lecturer examine more than one sessions continuously with different room which far away. Does not rarely in room placement, lecturer will placement in different building with far away in continuous sessions so raises final presentation for skripsi process will be late from initial scheduling because moving process. With the development of science and technology management, scheduling process should be done better. One of algoritm can use for recommendation of optimal final presentation for thesis is genetic algoritm where this algorithm can use for finished complex problems with many variable and result set of optimal solutions. In the formation of chromosome that used is permutation representation, the crossover process that used is one cut point crossover method, the mutation process that used is one random mutation method, the evaluation process with get fitness value each individual, the selection method that used is elitism. In the test result of room placement final presentation for thesis in one day obtained highest average fitness value is 1,000 in combination of cr 0,5 and mr 0,5, population size is 90, and generation size is 90. Room placement solution that use system can offer optimal scheduling with does not break the constraint at all.